2003
DOI: 10.1046/j.1600-065x.2003.00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Effector mechanisms in transplant rejection

Abstract: Antigens, provided by the allograft, trigger the activation and proliferation of allospecific T cells. As a consequence of this response, effector elements are generated that mediate graft injury and are responsible for the clinical manifestations of allograft rejection. Donor-specific CD8+ cytotoxic T lymphocytes play a major role in this process. Likewise, CD4+ T cells mediate delayed-type hypersensitivity responses via the production of soluble mediators that function to further activate and guide immune ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
122
0
17

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(139 citation statements)
references
References 129 publications
0
122
0
17
Order By: Relevance
“…+ T cells, considered to have a major role in graft rejection [39]. In fact, a recent study has shown that allogeneic ASCs are susceptible for lysis by both cytotoxic CD8 + T cells and NK cells [40].…”
Section: Cd8mentioning
confidence: 99%
“…+ T cells, considered to have a major role in graft rejection [39]. In fact, a recent study has shown that allogeneic ASCs are susceptible for lysis by both cytotoxic CD8 + T cells and NK cells [40].…”
Section: Cd8mentioning
confidence: 99%
“…B y recognizing allogeneic MHC class I Ags and exerting cytolytic function, primarily via granzyme and perforin mechanisms, alloreactive CD8 T lymphocytes are major effectors in the allograft rejection cascade (1,2). Despite their key role in transplant immunology, however, the mechanisms of alloreactive CD8 T cell activation and memory formation are far from being elucidated.…”
mentioning
confidence: 99%
“…9 These cells can be activated by recognizing allogeneic antigen directly or indirectly and can mediate delayed-type hypersensitivity responses to damage the allograft. 10 In addition, CD4 1 T cells can be differentiated into various subsets. CD4…”
Section: Cd4mentioning
confidence: 99%